The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1590/s0303-76572003000200003
|View full text |Cite
|
Sign up to set email alerts
|

Estudo epidemiologico dos coletores de lixo seletivo

Abstract: O artigo aborda epidemiologicamente o perfil dos coletores de lixo seletivo e descreve as lesões musculares e acidentes de trabalho mais freqüentes. Este estudo transversal foi desenvolvido com duas empresas (denominadas como empresa A e empresa B), em Porto Alegre, selecionando-se 50 funcionários aleatoriamente (presentes e aptos nos dias das entrevistas para a pesquisa) e aos quais foi aplicado um questionário. A Média de idade da amostra foi de 34 e 22 anos para a empresa A e B, respectivamente. Cerca de 66… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 12 publications
(3 reference statements)
1
3
0
5
Order By: Relevance
“…The mean age found among the UCWs in this study was compatible with the mean of other studies in the same category 17,21 , thus showing the relatively Young profile of this category, which can reflect on physical demands of the developed tasks, leading to overload for the body.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The mean age found among the UCWs in this study was compatible with the mean of other studies in the same category 17,21 , thus showing the relatively Young profile of this category, which can reflect on physical demands of the developed tasks, leading to overload for the body.…”
Section: Discussionsupporting
confidence: 90%
“…The possible consequence for that is the submission to difficult conditions in this activities and the low interlocution with the management for better work conditions. The intake of alcohol among these workers is very high 21,23,24 . This study demonstrated high frequency of alcohol intake at least once a week, and this result is compatible with other studies in the same category, which indicate the stressful activity of public waste collection as the precursor of the onset of alcohol intake, calling the attention to the risk of alcoholism among waste collectors 23,24 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No que se refere, ainda, à afirmação anterior, Santos [17], descreve os riscos que o coletor de resíduos está sujeito durante o trabalho são de ordem mecânica (cortes, perfurações, atropelamentos, quedas), ergonômica (esforço excessivo), biológica (agentes biológicos), química (substâncias químicas tóxicas) e social (falta de treinamento para a atividade). Existem também os riscos de acidentes ocasionados por diversos fatores como: acondicionamento inadequado do lixo, mão de obra desqualificada, excesso de peso a que são submetidos e uso inadequado dos equipamentos de proteção individual [10].…”
Section: Introductionunclassified